Zooplankton is more strongly controlled by nutrients than predation in a vegetation-free Mediterranean shallow lake: a mesocosm experiment. Issue 4 (2nd October 2018) - Fernández-Aláez, Camino; Trigal, Cristina; García-Girón, Jorge; Fernández-Aláez, Margarita
ABSTRACT: We conducted a mesocosm experiment in a Mediterranean shallow lake dominated by Myriophyllum alterniflorum to assess the effects of nutrient enrichment and fish addition on the composition and functional structure of zooplankton assemblages when macrophytes are absent. Fish ( Achondrostoma arcasii ) and nutrients were added in 9 combinations: 3 fish densities (fresh mass: 0, 4, and 20 g m −2 ) and 3 nutrient loading (nitrogen–phosphorus final concentration increases of 0–0, 1–0.1, and 5–0.5 mg L −1 ). After 5 weeks, macrophytes were cut and removed. The results suggest that the response of zooplankton to increased nutrient loading and fish densities was modulated by the presence or absence of vegetation. Small cladocerans were the most important group to differentiate between vegetated and nonvegetated phases, and their biomass significantly decreased after vegetation removal. Throughout the phase without macrophytes, the biomass of cyclopoids and Daphnia longispina increased in the most fertilized mesocosms while phytoplankton biovolume decreased along the nutrient gradient, mainly as a result of the decline of cyanobacteria; therefore, the bottom-up effect was transferred to zooplankton. The effect of fish on total zooplankton biomass was negligible; however, the response of D. longispina to fish densities was modulated by nutrient concentration. Zooplankton:phytoplankton biomass (ZB:PB) and Daphnia :phytoplankton biomass (DB:PB) ratios showed that the trophic cascade was strengthened in the most eutrophic conditions. We suggest that, in vegetation-free Mediterranean shallow lakes, eutrophication management strategies based on the control of phytoplankton production could be achieved even when a moderate fish population is maintained.